Integrated System Development to Support the Implementation of Tri Dharma of Higher Education by Lecturers at the Indonesia Civil Pilot Academy of Banyuwangi - Hasyim As ari; Miko Andi Wardana; Putra Wicaksono; Fajar Islam (Asosiasi Dosen Muda Indonesia, 2025)
Abstract: In the pursuit of producing quality professional human resources in the field of aviation, Indonesian Aviation Academy (API) Banyuwangi is one of the government agencies under the educational institutions. The Banyuwangi Ministry of Transportation institute gave its best shot, requiring an appealing integrated information system for better activities by lecturers and academic staff in applying education, research, and community service. This system shall make work more effective and efficient by digitalizing academic planning recording, and reporting as well as providing Collaborative features amongst researchers’ scientific publication repositories that may be stored quite tidily. Besides this platform for proper transparent Community Service Programs it also marks a strategic move forward toward making API Banyuwangi one of the Leading globalized aviation education institutions which Government’s digital transformation reform agenda in Higher Education supports. Keywords: API Banyuwangi, going digital, teachers, digital change, academic info system.